Re-identifying the rebound: What about asymmetry? - Frondel, Manuel; Vance, Colin (Technische Universität Dortmund, 2011)
Rebound effects measure the behaviorally induced offset in the reduction of energy consumption following efficiency improvements. Using panel estimation methods and household travel diary data collected in Germany between 1997 and 2009, this study identifies the rebound effect in private transport by allowing for the possibility that fuel price elasticities – from which rebound effects can be derived – are asymmetric. This approach rests on evidence that has emerged from the empirical literature suggesting that the response in individual travel demand to price increases is stronger than to decreases. With a rebound effect estimate for single-vehicle households of 58%, our result is in line with a recent German study by FRONDEL, PETERS, and VANCE (2008), but is substantially larger than those obtained from other studies. Moreover, we fail to reject the hypothesis that the magnitude of the response to a price increase is equal to that of a price decrease.
Discussion Paper / SFB 823;18/11
Keywords: automobile travel; panel estimation models; 310; 330; 620